The Correlation Between Erectile Dysfunction and Coronary Heart Disease in Men at RSUP. Prof. Ngoerah - Wangsadinata, Stanislaus Clifton; I Gusti Ngurah Pramesemara; I Made Putra Swi Antara; I Nyoman Gede Wardana (Universitas Airlangga, 2025)
Background : Coronary heart disease (CHD) has become one of the major economic burdens globally, as CHD has been the leading cause of mortality worldwide for the past 25 to 30 years. One of the factors that plays a role as a predictor of coronary heart disease is erectile dysfunction. Objective : To investigate the correlation between erectile dysfunction and coronary heart disease in male patients at RSUP Prof. Ngoerah. Methods : This research is an observational analytic study with a case-control design. Erectile dysfunction was measured using the IIEF-5 questionnaire, which consists of 5 items. Other risk factors were measured using a patient data questionnaire. The study sample consisted of 50 participants, divided into 25 cases and 25 controls. The case samples were male patients aged 25–60 with a history of coronary heart disease who were visiting or receiving treatment at the Cardiology Outpatient Clinic, Integrated Cardiac Services Building, RSUP Prof. Ngoerah, Denpasar. The control samples had the same criteria as the case samples but had no history of coronary heart disease. Results : A significant relationship was found between erectile dysfunction and coronary heart disease (p=0.049), with an OR of 9.33 (95% CI 1.05–82.8). Conclusion : There is a significant relationship between erectile dysfunction and coronary heart disease. Patients with erectile dysfunction have a 9.33 times higher likelihood of having coronary heart disease.